Social-economic Challenges of Population Aging for the National Economy (Economic journal of Lesya Ukrainka Volyn National University, 2015)
The current state of the worldʼs population aging is analysed in the article. It was found that the XXI century would be the century of aging unlike the previous «century of world population growth». According to UN projections of 2050 the proportion share of elderly peole will double. This is a significant challenge to the pension system, job market, financial market and so on. It was established that the main consequences of aging population are increasing the demand for public goods (especially medicine), state social expenditures, increasing the taxes of the economically active population, market interest rates and so on. The international institutions forecasts dealing with demographic trends of 2050 were systematized. The specificity of this social and economic phenomenon in Ukraine was studied. It was determined that the demographic situation in Ukraine is characterized by reduced birth rate, increased mortality, increased life expectancy and etc. In the structure of pensioners income there is a significant gap in pension as to regions and types of people holding them. The basic directions of reforming the economic system of Ukraine, including de-shadowing of the economy, improving the investment climate in the country, implementing a pension reform were suggested
Keywords: population aging, the economic effects of population aging, social and economic welfare, pension reform